THE INFLUENCE OF SODIUM ORTHOVANADATE ON THE P53 AND CASPASE 3 EXPRESSIONS IN BETA CELLS DIABETIC MICE MODEL - Hidayati, Sholihatil; Khotib, Junaidi; ., Suharjono (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study was designed to investigate the influence of sodium orthovanadate (SOV) on the P53 and caspase 3 expressions in beta cells of alloxan-induced diabetic mice. Methods: Mice were divided into 5 groups i.e. (1) control group, (2) diabetic group and (3-5) SOV-treated diabetic groups at dose of 16, 32 and 64 mg/kgBW respectively. Diabetic mice model was induced by intraperitoneal administration of alloxan monohydrate at the dose of 200 mg/kgBW. Diabetic state was occurred on third day after alloxan injection and then started the treatment of SOV for 7 days. The pancreas was harvested on ten day after treatment and was stained using routine histology staining with haematoxylin-eosin (HE) and aldehyde fuchsin (AF) for morphological analysis and immunohistochemical approaches to observe the expressions of P53 and caspase 3 in pancreas. Results: Diabetic condition was shown by the increasing of fasting blood glucose levels from 59.1±11.2 mg/dl to 310.6±107.2 mg/dl on third day. Administration of SOV with dose 16, 32 and 64 mg/kgBW reduced the fasting blood glucose levels after 7 days treatment (p<0.05) at diabetic mice, respectively 303,0±126,8, 231,8±57,1 and 75,6±40,8 mg/dl. The results of histology staining showed that SOV reduced apoptosis in beta cells. Using immunohistochemical approaches, SOV might decreased the P53 and caspase 3 expressions in beta cells alloxan-induced diabetic mice (p<0.05). Conclusion: This study reveals that the administration of SOV on diabetic mice led to the decreasing of P53 and caspase 3 expression that cause the decreasing of apoptosis in beta cells.